2014
DOI: 10.1378/chest.13-2946
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Acute Respiratory Disease in Current and Former Smokers With and Without COPD

Abstract: Although acute episode of respiratory disease rates are higher in subjects with COPD, risk factors are similar, and at a population level, there are more episodes in smokers without COPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
70
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 76 publications
(73 citation statements)
references
References 37 publications
2
70
1
Order By: Relevance
“…Poor nutritional status, diabetes, low FEV 1 was other causes of morbidity after discharge. These findings were in similar to another study by Steer et al 35 The duration of exacerbation was significantly associated with its severity and season, which is in accordance to other studies. [29][30][31] It was also shown that a patient with exacerbations in the past is more likely to show them in future too, most of them requiring hospitalization.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Poor nutritional status, diabetes, low FEV 1 was other causes of morbidity after discharge. These findings were in similar to another study by Steer et al 35 The duration of exacerbation was significantly associated with its severity and season, which is in accordance to other studies. [29][30][31] It was also shown that a patient with exacerbations in the past is more likely to show them in future too, most of them requiring hospitalization.…”
Section: Discussionsupporting
confidence: 93%
“…This was in accordance to other studies by Husebo et al and others. [32][33][34][35] There was no difference in the number of exacerbations between the smokers and ex-smokers. This could conclude that the stoppage of the smoking was too late.…”
Section: Discussionmentioning
confidence: 87%
“…Both of these groups have been demonstrated to have significant respiratory symptoms and impairment, in some cases greater than subjects with GOLD stage 1 COPD, and as we observed, they are also often treated with long-acting bronchodilators and inhaled corticosteroids despite no evidence to support that practice (9,10,19,29). We can only speculate about why no relationships between acute respiratory events and FEV 1 decline were observed in these subjects.…”
Section: Discussionmentioning
confidence: 53%
“…Although many COPD treatments reduce exacerbation frequency and some studies suggest that inhaled therapies may reduce FEV 1 decline (7,8), there is no information about the association between these two key disease features. Many smokers without COPD also suffer acute respiratory events that appear clinically similar to classic exacerbations in those with established COPD (9,10). Whether such respiratory events accelerate lung function loss or lead to the development of COPD is unknown.…”
Section: Measurements and Main Resultsmentioning
confidence: 99%
“…Conversely, COPD exacerbations appear to impact the risk of cardiovascular events [70]. Although acute exacerbations of respiratory symptoms occur more frequently in patients with COPD, they also occur with significant frequency in smokers without COPD, suggesting that they are not specific for COPD [71,72]. Patients with COPD have a similar prevalence of sleep apnoea as the general population.…”
Section: Phenotypingmentioning
confidence: 99%